Workshop and International Company Visit: Export Opportunities for Aceh's Creative Economy Products - Halim, Hendra; Kesuma, T. Meldi; M. Ridha Siregar; Muhammad Haris Riyaldi; Nurma Sari; Novi Indriyani Sitepu; Teuku Muhammad Syahrizal; Khairil Umuri; Eka Nurlina; Dewi Suryani Sentosa; Sartiyah; Suriani; Susanna; M. Shabri Abdul Majid; Syahriyal; Fitrah Afandi ZT; Stephanus TW; Eddy Gunawan; Dzacky Muharram Rani; Ahmad Nizam; Annisa Keumala Dewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Collaboration with Faculty of Economics and Business Lecturers, Research Center for Communication Marketing, Tourism & Creative Economy at Syiah Kuala University, Business Indonesia Singapore Association (BISA), and Cloud Retail PTE Ltd aims to overcome constraints in international market access, global understanding, and building robust business networks. Through training at Syiah Kuala University and a company visit to Cloud Retail PTE Ltd in Singapore, participants gain profound insights into product packaging, export licensing procedures, and distribution channels. The holistic training method, combining theory and practical experience, empowers participants to optimize their business potential in the creative economy and access the global market. Evaluation indicates enhanced participant understanding and readiness, with recommendations for strengthened collaboration, ongoing training, business network development, monitoring and evaluation, and advanced program development.